COVID-19 vaccine acceptance among Malaysians - Yi-Fan Tan; Meng-Chew Leow; Lee-Yeng Ong (International Journal of Public Health Science (IJPHS), 2023)
Since the first declaration of the coronavirus (COVID-19) outbreak, massive number of efforts have been taken to develop and deploy the COVID-19 vaccines. However, there might be hesitation towards the vaccines as there were reports of side effects. This study evaluates the COVID-19 vaccination acceptance of the Malaysian public via an online survey hosted in a COVID-19 vaccination acceptance roadshow event. This study gives an insight to the level of vaccination acceptance of the Malaysian public, while at the same time highlights the possible reasons that vaccination rejection may occur in perspectives that are specific to Malaysians. The overall vaccination acceptance of the Malaysian public is high, as most of them either prefer to get vaccinated or already been vaccinated. Most of them have good knowledge on the safety of COVID-19 vaccines and the importance of vaccination. However, the respondents may have differing opinions on their confidence level towards vaccines by specific manufacturers. These findings give an insight into the COVID-19 vaccination acceptance level of the Malaysian public and may possibly aid in effort for vaccination acceptance should there be any form of pandemic as severe as the COVID-19 pandemic occurring in the future.